Analisis Elemen Visual Pada Komik “Pupus Putus Sekolah” - Yuliaqanita, Adinda; Amanda, Romauli; Salsabila, Robiah; Khoirunisa, Shafira (Fakultas Desain Universitas Komputer Indonesia, 2024)
Digital comics are currently gaining popularity among many people, especially teenagers. Not only serving as a form of entertainment, they can also be utilized as a means of conveying information. The objective of this research is to understand the use of visual elements in conveying messages and information through the comic